2003
DOI: 10.1007/s10038-003-0052-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel 2026G→C mutation of the MRP2 gene in a Japanese patient with Dubin-Johnson syndrome

Abstract: Dubin-Johnson syndrome is a recessive inherited disorder with conjugated hyperbilirubinemia caused by a dysfunction of multidrug resistance protein 2 (MRP2) on the canalicular membrane of hepatocytes. A mutational analysis of the MRP2 gene was carried out in three Japanese patients and their family members. In two patients, the homozygous mutations c.1901del67 and c,2272del168 were found. In the third patient, a )24C fi T polymorphism and the two mutations c.1901del67 and 2026G fi C were detected. The 2026G fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…The reported missense mutations involving the two ABC in the MRP2 include G676R and R768W in the first ABC and Q1382R in the second ABC (11,13,17,18). The functional study showed that R768W causes deficient maturation and impaired sorting of protein, Q1382R impairs the substrateinduced ATP hydrolysis, and Del R1392, M1393 leads to impaired maturation and trafficking of protein from endoplasmic reticulum (ER) to the Golgi complex (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The reported missense mutations involving the two ABC in the MRP2 include G676R and R768W in the first ABC and Q1382R in the second ABC (11,13,17,18). The functional study showed that R768W causes deficient maturation and impaired sorting of protein, Q1382R impairs the substrateinduced ATP hydrolysis, and Del R1392, M1393 leads to impaired maturation and trafficking of protein from endoplasmic reticulum (ER) to the Golgi complex (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Various polymorphisms in the MRP2 gene contribute to the etiology of the Dubin-Johnson syndrome (Paulusma et al, 1996;Wada et al, 1998;Tsujii et al, 1999;Mor-Cohen et al, 2001;Tate et al, 2002;Materna and Lage, 2003;Wakusawa et al, 2003). It was shown that single nucleotide changes like the 3517 A/T transition in exon 25 are associated with lower efflux of MRP2 substrates and altered distribution of the protein in transfected cells (Mor-Cohen et al, 2001;Keitel et al, 2003).…”
Section: Meyer Zu Schwabedissen Et Almentioning
confidence: 99%
“…The absence of functional MRP2 is the molecular basis of transport defect of DJS (283). Many single nucleotide polymorphisms in DJS patients have been reported (Table 2) (118,(284)(285)(286)(287)(288). These include C-24T (promoter), G1249A (exon 10), G2026C (exon 16), T2125C (exon 17), C2302T (exon 18), C2366 (exon 18), A3517T (exon 25), G3449 (exon 25), C3972T (exon 28) and G4348A (Exon 31) ( Table 2).…”
Section: Pharmacogenetics Of Mrpsmentioning
confidence: 99%